2015
DOI: 10.1016/j.jascer.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of amino-functionalized mesoporous silica sheets and their application for metal ion capture

Abstract: a b s t r a c tNovel mesoporous silica sheets with surface amino-functional groups (sheet-NH 2 ) were prepared for the efficient adsorption of aqueous metal ions. The sheet-NH 2 were synthesized by a dual-templating process using Pluronic P123 and N-palmitoyl-l-alanine as templates. Two silicone regents were used to form the silica framework: tetraethoxysilane and 3-aminopropyltriethoxysilane. In the synthetic process, the as-prepared silicate was refluxed in ethanol to remove the organic templates remaining f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…The extra peaks, apart from the MSN peaks, in TB MSN at 2,830, 2,910 and 3,518 cm À1 clearly show the presence of TB in MSN. These peaks of TB and MSN agree well with previous reports (Ganguly et al 2013;Nakanishi et al 2015;Khosraviyan et al 2016). HR-TEM micrographs revealed the size, shape, and dispersity of TB MSN.…”
Section: Discussionsupporting
confidence: 92%
“…The extra peaks, apart from the MSN peaks, in TB MSN at 2,830, 2,910 and 3,518 cm À1 clearly show the presence of TB in MSN. These peaks of TB and MSN agree well with previous reports (Ganguly et al 2013;Nakanishi et al 2015;Khosraviyan et al 2016). HR-TEM micrographs revealed the size, shape, and dispersity of TB MSN.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the n value greater than 1 showed that the adsorption of Zn(II) onto PAM‐2.5b was favorable. The maximum adsorption capacity was greater than the value of various reported adsorbent for Zn(II) removal (Table ) , indicating that the PAMs in situ thermosynthesized by PDILMs could effectively remove Zn(II) from waste water.…”
Section: Resultsmentioning
confidence: 86%
“…The absorption band at 949 cm −1 (Si-OH) indicated the high concentration of the silanol group [23]. After calcination at 620°C for 6 h, the absorption band at 1065 cm −1 (Si-O-Si asymmetric stretching) became sharper and the absorption band at 949 cm −1 (Si-OH bending vibration) disappearred [24] due to condensation of the silanol group, changing into the Si-O-Si network [25]. Si-O-Si symmetric vibration stretching shifted from 806 cm −1 to 789 cm −1 , and the intensity of the absorption band increased due to the formation of the SiO 2 network [26].…”
Section: Morphology and Characterization Studies Of Hollow Silica Micmentioning
confidence: 99%